2020
DOI: 10.1002/cncr.32573
|View full text |Cite
|
Sign up to set email alerts
|

Nab‐paclitaxel in older patients with non–small cell lung cancer who have developed disease progression after platinum‐based doublet chemotherapy

Abstract: Background The selection of later‐line treatment for older patients with AJCC (version 7) stage IV non–small cell lung cancer (NSCLC) remains controversial. Nanoparticle albumin–bound (nab)‐paclitaxel is approved with carboplatin for the first‐line treatment of patients with NSCLC and subgroup analysis of phase 3 data has suggested superior survival in older patients. Methods The authors conducted a phase 2 study of nab‐paclitaxel in 42 patients aged ≥70 years who had been treated previously with a platinum do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…Together, these results suggest that the nab‐paclitaxel combination might be the preferred approach in elderly patients. The current trial from Weiss et al built on these observations and extended the applicability of previous results to the use of single‐agent nab‐paclitaxel in the second‐line setting.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…Together, these results suggest that the nab‐paclitaxel combination might be the preferred approach in elderly patients. The current trial from Weiss et al built on these observations and extended the applicability of previous results to the use of single‐agent nab‐paclitaxel in the second‐line setting.…”
mentioning
confidence: 62%
“…In this issue of Cancer , Youn et al and Weiss et al have provided evidence regarding the outcomes of elderly patients with metastatic NSCLC (mNSCLC) who were treated with immunotherapy in a real‐world setting and clinical trial experience using single‐agent nab‐paclitaxel chemotherapy, respectively. Although historically single‐agent chemotherapy has been the preferred modality for therapy in elderly patients, clinical trials evaluating carboplatin‐based doublet therapy in treatment‐naive patients have demonstrated superiority to standard single agents, establishing these regimens as the current standard of care for fit elderly patients .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite some disadvantages, checkpoint inhibitors possess a great prospect. The recent findings suggest that PD-1/PD-L1 inhibitors may be combined with other immunotherapies or traditional treatments to enhance efficacy relative to that using PD-1/PD-L1 therapy alone, which always exhibit higher response rates, reducing adverse reaction and drug resistance (Li J. et al, 2019;Zhang et al, 2019;Li et al, 2020;Shao et al, 2020;Sonpavde et al, 2020;Wan et al, 2020;Weiss et al, 2020;Zhang et al, 2020). Some researchers have shown the prospects of anti-PD-L1 and anti-CTLA-4 combination therapy, which revealed PD-L1:CD80 (CTLA-4 ligand) cis-heterodimerization inhibited both PD-L1: PD-1 and CD80:CTLA-4 interactions.…”
Section: Prospectsmentioning
confidence: 99%